The influence of isobuthyl methylxhantine (IMX) and separation time on viability of spermatozoa and effectiveness of separation using egg albumin column - Sianturi, R.G; Situmorang, P; Triwulanningsih, Elsa; Sugiarti, T; Kusumaningrum, D.A (Indonesian Animal Sciences Society, 2004)
Supplementation of 3-isobuthyl-1-1-methylxanthine (IMX), as a cAMP inhibitor phosphodiesterase and could raise sperm motility, is expected to optimize the X and Y sperm separation. The purpose of this research was to observe the effect of IMX supplementation and separation time on the quality of separated sperm and the effectiveness of the method of sperm separation. Completely randomized design with 2 x 2 factorial was used in this research. The first factor was IMX (0.0 and 0.5 mM) while the second factor was separation time (10 and 30 minutes). The parameters observed were sperm concentration, the percentages of sperm motility, live sperm, sperm with intact apical ridge and the ratio of spermatozoa X and Y which measured by morfometric of head sperm square. IMX supplementation did not affect sperm concentration both on 10 or 30 minutes. The 30-minute separation time significantly reduced sperm motility in upper fraction while the addition of IMX significantly reduced sperm motility in lower fraction. There were no significant differences on the percentage of live sperm and sperm with intact apical ridge in every treatment even in upper or lower fraction. The albumin column sperm separation in this research changed the ratio of X and Y spermatozoa from 49.7% : 50.3% (fresh semen) to 65.1-84.0% : 16.0-34.9% in upper fraction; and to 24.0- 30.0% : 70.0-75.9% in lower fraction. The addition of IMX increased significantly X spermatozoa percentage (65.1 to 84.0%) and reduced significant Y-spermatozoa percentage (34.9% to 16.0%) in upper fraction. There was no significant differences on the ratio of X and Y spermatozoa between 10 and 30-minute of separation time treatment. In conclusion, the albumin column separation technique can be used to separate X and Y spermatozoa with the duration of 10 to 30 minutes separation time and did not severely affect the quality of separated sperm. The presence of IMX in separation media has no effect on the sperm separation effectiveness. Â Key words: Sperm separation, isobuthyl methylxanthine, X and Y spermatozoa, albumin column